Applying laser scanning technology to studying alluvial flume-bed topography in laboratory conditions - Marta Kiraga; Mateusz Razumnik; Zbigniew Popek; Leszek Chmielewski (Acta Scientiarum Polonorum. Formatio Circumiectus, 2018)
The aim of the research was to compare alluvial bed topography description in laboratory conditions using the “traditional”, currently applicable method with an original approach, based on LiDAR technology. LiDAR application in local scours shape investigation in based on the grounds of introducing the autonomic measuring module, which, placed above the bed on dedicated controllable arrangement of guideways, describes the landform as a cloud of coordinates. The result of the performed experiment was obtainment of point clouds (x, y, z), reflecting the bed shape before and after local scour formation during twenty measurement series with varying hydraulic conditions. Objects of the study were basic geometry properties of the scour hole and its volume. The measurement with laser scanner technology application allowed for obtaining much more accurate results in shorter time, comparison to disc probe survey, and also relatively fast conversion of numerical data into figures. The device equipped with portable computer, precise stepper motors and dedicated software permitted the introduction of automation into laboratory work. The effect is not only measurements accuracy, but also significant acceleration of data gathering. The adopted grid is characterized by significant density, which – in connection with meaningfully high accuracy – allows very precise surface description. Bed shape can be presented in numerical or graphical form. It must be pointed out that disc probe method application would never give such accuracy as in the case of introducing laser scanning technology in similar studies.